Accelerated, Microwave‐Assisted, and Conventional Solvent Extraction Methods Affect Anthocyanin Composition from Colored Grains. Issue 2 (February 2014) - Abdel‐Aal, El‐Sayed M.; Akhtar, Humayoun; Rabalski, Iwona; Bryan, Michael
Abstract Anthocyanins are important dietary components with diverse positive functions in human health. This study investigates effects of accelerated solvent extraction (ASE) and microwave‐assisted extraction (MAE) on anthocyanin composition and extraction efficiency from blue wheat, purple corn, and black rice in comparison with the commonly used solvent extraction (CSE). Factorial experimental design was employed to study effects of ASE and MAE variables, and anthocyanin extracts were analyzed by spectrophotometry, high‐performance liquid chromatography‐diode array detector (DAD), and liquid chromatography–mass spectrometry chromatography. The extraction efficiency of ASE and MAE was comparable with CSE at the optimal conditions. The greatest extraction by ASE was achieved at 50 °C, 2500 psi, 10 min using 5 cycles, and 100% flush. For MAE, a combination of 70 °C, 300 W, and 10 min in MAE was the most effective in extracting anthocyanins from blue wheat and purple corn compared with 50 °C, 1200 W, and 20 min for black rice. The anthocyanin composition of grain extracts was influenced by the extraction method. The ASE extraction method seems to be more appropriate in extracting anthocyanins from the colored grains as being comparable with the CSE method based on changes in anthocyanin composition. The method caused lower structural changes in anthocaynins compared with the MAE method. Changes in blue wheat anthocyanins were lower in comparison with purple corn or black rice perhaps due to the absence of acylated anthocyanin compounds in blue wheat. The results show significant differences in anthocyanins among the 3 extraction methods, which indicate a need to standardize a method for valid comparisons among studies and for quality assurance purposes.